BREEDING WORK WITH KAZAKH WHITE-HEADED CATTLE WITH THE FORMATION OF THE NECESSARY GENE POOL - Nassambayev, E.; Akhmetalieva, A. B.; Nugmanova, A. E.; Kulbaev, R. (Ғылым және білім=Наука и образование=Science and education - № 4-3 (69), 2022)
The most obvious and important goal of selection is the maximum receipt of the economic effect from the implementation of activities aimed at increasing selection and breeding work. An equally important direction on the way to creating highly efficient animal husbandry is the widespread use of economic models. In practical work, the breeding value of an animal is determined by many features with different economic significance. According to the test results of Kazakh white-headed bulls on their own productivity, they were carried out in accordance with the «Instructions for evaluating beef bulls on their own productivity and offspring quality» (Almaty, 2010) - No. 1 dated December 26, 2009. checking and evaluating beef bulls for the quality of their offspring and testing bulls for their own productivity (Order of the Ministry of Agriculture of the Republic of Kazakhstan dated 19.07.2010, No. 456, as well as the «Instruction for grading cattle of beef breeds» (Order of the Ministry of Agriculture of the Republic of Kazakhstan dated 16.06 .2000, No. 162)). The studies were carried out in «Aisulu» farm, «Dongelek» farm, «Hafiz» farm, «Chapaevsky» LLP, «Eset» farm, «Zhannat» farm, «Tolegen» farm, «Alem» farm and «Naryn» farm West Kazakhstan region. The results of the study showed that in the farm «Aisulu» the live weight of bulls when removed from the test at the age of 15 months. amounted to 401.7 kg, with an average daily gain of 810.8 g with a feed consumption of 7.0 feed units. Also, the indicators of the class and index evaluation of bulls based on the results of their testing for their own productivity had a similar trend in the farms of the «Dongelek» farm, «Hafiz» farm, «Eset»и farm and «Naryn» farm and corresponded to the standard and higher. Наиболее очевидной и важной целью селекции выступает максимальное получение экономического эффекта от проведения мероприятий направленных на повышение селекционно-племенной работы. Не менее важным направлением на пути создания высокоэффективного животноводства является повсеместное использование экономических моделей. В практической работе племенную ценность животного обусловливают множество признаков с разной хозяйственной значимостью. По результатам испытания бычков казахской белоголовой породы по собственной продуктивности проводили в соответствии с «Инструкцией по оценке быков-производителей мясных пород по собственной продуктивности и качеству потомства» (Алматы, 2010) - №1 от 26 декабря 2009 г. решение НТС МСХ РК, проведение проверки и оценки быков-производителей мясных пород по качеству потомства и испытание бычков по собственной продуктивности (Приказ МСХ РК от 19.07.20 10 г., №456, а также «Инструкцией по бонитировке крупного рогатого скота мясных пород» (Приказ МСХ РК от 16.06.2000 г., №162)). Исследования были проведены в КХ «Айсулу», КХ «Донгелек», КХ «Хафиз», ТОО «ПЗ Чапаевский», КХ «Есет», КХ «Жаннат», КХ «Толеген», КХ «Алем» и КХ «Нарын» Западно – Казахстанской области. Результаты исследования показали, что в КХ «Айсулу» живая масса бычков при снятии с испытания в возрасте 15 мес. составила – 401,7 кг, со среднесуточным приростом 810,8 г при затрате корма 7,0 кормовых единиц Также показатели классной и индексной оценки бычков по результатам их испытания по собственной продуктивности имели схожую тенденцию в хозяйствах КХ «Донгелек», КХ «Хафиз», КХ «Есет» и КХ «Нарын» и соответствовали стандарту и выше.
Keywords: научный журнал; ринц; отечественное издание; периодическое издание; журнал коксон; крупный рогатый скот; селекция крс; казахская белоголовая порода крс; Kazakh white-headed; breed; selection; gene pool; live weight; class